Correlated barrier hopping and ionic conduction mechanism in glycolic acid-doped alginate-PVA biopolymer electrolytes - N. M., Ghazali; Ahmad Salihin, Samsudin (Elsevier Ltd, 2024)
This study examines the electrical and dielectric properties of solid polymer electrolytes (SPEs) based on an alginate-PVA blend doped with glycolic acid (GA). The AC conductivity as a function of frequency was observed to conform to Jonscher’s power law. The dielectric permittivity, dielectric loss, and complex conductivity were analysed and fitted across a frequency range of 1 Hz to 1 MHz at room temperature. It was found that an increase in GA content directly enhances the number of charge carrier (ŋ), ionic mobility (μ), and diffusion coefficient (D) of the SPEs system. The frequency exponent (s) was calculated and the correlated barrier hopping (CBH) model was used to explain the behaviour of the s value with temperature. AC conductivity analysis further revealed that the system is governed by polaron hopping, influenced by the addition of H+ charge carriers in the SPEs matrix.